Global prevalence of cardiometabolic risk factors in the military population: a systematic review and meta-analysis - Fereshteh Baygi; Kimmo Herttua; Olaf Chresten Jensen; Shirin Djalalinia; Armita Mahdavi Ghorabi; Hamid Asayesh; Mostafa Qorbani (BMC Endocrine Disorders, 2020)
Abstract Background Although there are numerous studies on the global prevalence of cardiometabolic risk factors (CMRFs) in military personnel, the pooled prevalence of CMRFs in this population remains unclear. We aimed to systematically review the literature on the estimation of the global prevalence of CMRFs in the military population. Methods We simultaneously searched PubMed and NLM Gateway (for MEDLINE), Institute of Scientific Information (ISI), and SCOPUS with using standard keywords. All papers published up to March 2018 were reviewed. Two independent reviewers assessed papers and extracted the data. Chi-square-based Q test was used to assess the heterogeneity of reported prevalence among studies. The overall prevalence of all CMRFs, including overweight, obesity, high low-density lipoprotein (LDL), high total cholesterol (TC), high triglyceride (TG), low high-density lipoprotein (HDL), hypertension (HTN) and high fasting blood sugar (FBS) was estimated by using the random effects meta-analysis. A total of 37 studies met the eligibility criteria and were included in the meta-analysis. Results According the random effect meta-analysis, the global pooled prevalence (95% confidence interval) of MetS, high LDL, high TC, high TG, low HDL and high FBS were 21% (17–25), 32% (27–36), 34% (10–57), 24% (16–31), 28% (17–38) and 9% (5–12), respectively. Moreover, global pooled prevalence of overweight, generalized obesity, abdominal obesity and HTN were estimated to be 35% (31–39), 14% (13–16), 29% (20–39) and 26 (19–34), respectively. Conclusions The overall prevalence of some cardio-metabolic risk factors was estimated to be higher in military personnel. Therefore, the necessary actions should be taken to reduce risk of developing cardiovascular diseases. Systematic review registration number in PROSPERO CRD42018103345